2000
DOI: 10.1128/iai.68.12.6770-6776.2000
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CD14 and β2-Integrins in Activating Cells with Soluble and Particulate Lipopolysaccharides and Mannuronic Acid Polymers

Abstract: Lipopolysaccharide (LPS), a glycolipid present in the outer membrane of gram-negative bacteria, is a potent inducer of proinflammatory responses from cells of the monocytic lineage. LPS stimulation of monocytes results in cytokine production, one of the key events in the pathogenesis of gram-negative sepsis (4). The cell surface glycoprotein CD14 (membrane CD14 [mCD14]) has been identified as the principal LPS receptor on phagocytic leukocytes, enabeling them to be stimulated with picogram amounts of LPS (42,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Several previous studies have suggested that integrins participate in LPS signaling in macrophages (13,42,43). Furthermore, the binding of ligands to integrin ␣ v ␤ 3 was found to induce in NF-B activation (35), thus suggesting that integrin ␣ v ␤ 3 engagement influences an NF-B-dependent program of gene expression.…”
Section: Discussionmentioning
confidence: 93%
“…Several previous studies have suggested that integrins participate in LPS signaling in macrophages (13,42,43). Furthermore, the binding of ligands to integrin ␣ v ␤ 3 was found to induce in NF-B activation (35), thus suggesting that integrin ␣ v ␤ 3 engagement influences an NF-B-dependent program of gene expression.…”
Section: Discussionmentioning
confidence: 93%
“…Reagents-Poly-M (ϳ350 kDa, 92% M) was isolated from mucoid P. aeruginosa, and the batch was the same as that previously used (4,5 5 monocytes/well in 24-well dishes) were washed three times in Hanks' balanced salt solution (Invitrogen) and pretreated with a 10 g/ml concentration of the indicated mAbs or with 1 g/ml synthetic lipid IVA (compound 406) for 30 min at room temperature in serum-free RPMI 1640 medium (Invitrogen) with 0.01% L-glutamine, 40 g/ml gentamycin (referred to as RPMI hereafter) prior to addition of stimuli. Stimulation proceeded for 8 h at 37°C before supernatants were collected and stored at Ϫ20°C until assayed for TNF activity in the WEHI 164 clone 13 bioassay as described previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…3). Third, the TNFinducing capabilities of high molecular poly-M is greatly reduced by hydrolytic or enzymatic breakdown but restored or even enhanced when the resultant low molecular chains are attached to particles (4,5). Finally, the lack of response to poly-M in TLR4Ϫ/Ϫ cells rule out possible contamination with lipoproteins or lipopeptides.…”
Section: Tlr2 and Tlr4 Mediate Activation By Mannuronic Acid Polymersmentioning
confidence: 99%
See 2 more Smart Citations